The pedagogic device in higher education: a sociolinguistic analysis of the basic sciences field based on basil Bernstein’s Theory - Maria Bustamante; John Urrego (Cogent Education, 2025)
The hierarchical relationship between faculty and students in higher education is regarded as a key pedagogical practice in forms of power and in narrowing social and academic gaps for students with limited cultural capital. This qualitative study, drawing on Bernstein’s sociolinguistic approach, aims to analyze the rules of the pedagogic device in basic sciences to identify the features of classroom discourses and pedagogical practices that influence student retention. Empirical data were collected from narratives on faculty participants’ conceptions of higher education and their pedagogical practices in a course on student retention. The findings indicate that the pedagogic device fulfills the function of: (1) subtly organizing practices by exerting its control over the appropriation of the market-oriented official pedagogic discourse and (2) positioning students in either advantageous or disadvantageous locations within the academic field. The importance of recontextualization is emphasized in terms of facilitating knowledge access and maintaining appropriate levels of complexity in basic sciences teaching, such as mathematics, physics, chemistry and statistics, to reduce educational inequality.